Draft Whole-Genome Sequence of the Alkane-Synthesizing Polar Cyanobacterium Pseudanabaena biceps Strain O-153 - Péquin, Bérangère (Microbiol Resour Announc, 2020)
Alkane biosynthesis by polar cyanobacteria has not yet been reported. We present here the draft whole-genome sequence of an alkane-synthesizing polar cyanobacterium, Pseudanabaena biceps strain O-153. The genes coding for the two key enzymes involved in the alkane biosynthetic pathway were found contiguously in the genome.